2018
DOI: 10.1002/hbm.23981
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation with single‐element transcranial focused ultrasound in human thalamus

Abstract: Transcranial focused ultrasound (tFUS) has proven capable of stimulating cortical tissue in humans. tFUS confers high spatial resolutions with deep focal lengths and as such, has the potential to noninvasively modulate neural targets deep to the cortex in humans. We test the ability of single-element tFUS to noninvasively modulate unilateral thalamus in humans. Participants (N = 40) underwent either tFUS or sham neuromodulation targeted at the unilateral sensory thalamus that contains the ventro-posterior late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
247
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(259 citation statements)
references
References 59 publications
7
247
2
3
Order By: Relevance
“…[7] Here we demonstrate, that the target for the new TPS technique can be spatially distinct, highly focal, and is not restricted to superficial layers of the brain. [7] Here we demonstrate, that the target for the new TPS technique can be spatially distinct, highly focal, and is not restricted to superficial layers of the brain.…”
Section: Introductionmentioning
confidence: 69%
“…[7] Here we demonstrate, that the target for the new TPS technique can be spatially distinct, highly focal, and is not restricted to superficial layers of the brain. [7] Here we demonstrate, that the target for the new TPS technique can be spatially distinct, highly focal, and is not restricted to superficial layers of the brain.…”
Section: Introductionmentioning
confidence: 69%
“…Existing FUS neuromodulation techniques use ultrasound pulses with low intensity to produce mechanical effects for neural and behavioral modulation with a negligible temperature increase 4 . Numerous studies have confirmed that FUS can noninvasively modulate neural activity and brain function in animal models 5,6 and humans 1,3 .…”
Section: Introductionmentioning
confidence: 97%
“…Technologies for noninvasive modulation of mammalian brain activity with spatiotemporal precision and cell-type specificity have long been desired for experimental investigation of intact neural systems. Compared with electric, magnetic, optical, and chemical stimuli that have been used by existing neuromodulation technologies, focused ultrasound (FUS) offers unique advantages as it can noninvasively deliver ultrasound energy through the intact human scalp and skull deep into the brain and focus at cortical areas 1,2 as well as deep brain areas 3 with high spatial selectivity. Existing FUS neuromodulation techniques use ultrasound pulses with low intensity to produce mechanical effects for neural and behavioral modulation with a negligible temperature increase 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Transcranial focused ultrasound (tFUS) is a new and promising non-surgical low-energy technique that uses mechanical energy to modulate neuronal activity with high spatial resolution and adjustable depth of focus. tFUS has been used safely and effectively for cortical neuromodulation in mouse [1][2][3][4], rat [5,6], rabbit [7], sheep [8], pig [9] and monkey [10,11] models, and has also been demonstrated to be an effective method of transient cortical and sub-cortical neuromodulation in humans [12,13]. In humans, tFUS has been applied to the temporal cortex [14], primary somatosensory cortex (S1) [12,15], secondary somatosensory cortex (S2) [16], primary motor cortex [17,18] , primary visual cortex [19] and thalamus [13,20] .…”
Section: Introductionmentioning
confidence: 99%
“…tFUS has been used safely and effectively for cortical neuromodulation in mouse [1][2][3][4], rat [5,6], rabbit [7], sheep [8], pig [9] and monkey [10,11] models, and has also been demonstrated to be an effective method of transient cortical and sub-cortical neuromodulation in humans [12,13]. In humans, tFUS has been applied to the temporal cortex [14], primary somatosensory cortex (S1) [12,15], secondary somatosensory cortex (S2) [16], primary motor cortex [17,18] , primary visual cortex [19] and thalamus [13,20] . tFUS has been shown to affect the amplitude of evoked potentials [7,12,15], the power, phase and frequency of the electroencephalogram (EEG) [12,21]; the blood oxygen level dependent (BOLD) magnetic resonance imaging signal [7,17], as well as tactile [12,15] and reaction time [18] behaviour.…”
Section: Introductionmentioning
confidence: 99%